DIFFERENTIATION OF GROUP A STREPTOCOCCI WITH A COMMON R ANTIGEN INTO THREE SEROLOGICAL TYPES, WITH SPECIAL REFERENCE TO THE BACTERICIDAL TEST - Lancefield, Rebecca C. (The Rockefeller University Press, 1957)
In further study of streptococci having the R antigen, the bactericidal test has been used instead of the mouse protection test in investigating the type-specific M antigens of these organisms. The results have been confirmed by M anti-M precipitin tests, and a correlation between the M and T antigens of the strains has been shown. On the basis of a specific M antigen, type 28 has been shown to comprise Griffith's strain Small and four other R-containing strains. A number of other strains previously thought to belong to type 28 on the basis of R antigen reactions have now been identified as belonging either to type 2 or to a new type, designated 48, which shows a one-way cross-relationship to type 13. The bactericidal test is suggested as a useful method for assessing M antigen in group A streptococci and for establishing type-specificity by means of a biological test which is more widely applicable than the standard mouse protection test.